When critical thinking doesn’t work and why do we need common sense? - Kozachenko, Nadiia (Actual Problems of Mind, 2020)
The idea of critical thinking became popularity because people need methods of high-quality and fast information processing. But critical thinking does not work in every situation. The framework of methods, not filled with sufficient knowledge, is not self-sufficient and does not solve the problem of orientation in conditions of excess information, the facts depend on interpretation, and not everything in the human world can be systematized. Rationality, ordering and systematicity in human activity are presented on a fairly high scale and can be used rather as a guide, but not a support in everyday life. Everyday perception of information involves a quick response and thus differs from the qualitative reasoning that requires critical thinking. Thus, stereotype is often a much better helper than critical guidance, which is often implemented retrospectively. Thus, critical thinking has certain obstacles. These obstacles can be overcome by common sense. Compared with critical thinking, common sense is not so rational and methodical, but it is also important factor of evaluating information and decision-making and a significant factor of sociality. Common sense appears as a certain sense of self-adequacy and relevance in social practices, allows for subjective judgments that are common, reflects a sense of public good and common interest. Common sense performs an important function of awareness of the general norm, regulates permissible deviations from it, and in the individual sphere is a prerequisite for human ability to realize normality. In the epistemological aspect, common sense produces starting and ending points of reason, provides the opportunity to achieve intersubjective knowledge, and also plays the role of a kind of method of cognition, which is based on simplicity, naturalness and accessibility.